ANALYSIS OF THE INFLUENCE OF THE WORK ENVIRONMENT AND COMPENSATION ON WORK PERFORMANCE WITH JOB SATISFACTION AS A MEDIATION VARIABLE (Case Study SMAN 1 Margasari Tegal Regency) - Lukito Oki Hermawan; Kusuma Chandra Kirana; Epsilandri Septyarini (STKIP Singkawang, 2023)
Research aims to find out the influence of the work environment, compensation, and job satisfaction on Job Performance and know the influence that occurs indirectly on job satisfaction that acts as a mediator in SMAN 1 Margasari Tegal Regency. Quantitative descriptive research was used by researchers in this study. All Teachers and Staff Employees from SMAN 1 Margasari Tegal Regency became the object of this research. In the study, questionnaires became a data collection method used by researchers, with 52 respondents as sampling techniques.Validity and reliability tests are utilized by researchers to check records high-quality, with information analysis strategies used, particularly classical assumption checks, multiple linear regression exams, hypothesis checks and sobel exams. based at the outcomes of studies that has been accomplished suggests that the work surroundings has a extensive positive impact on paintings performance, reimbursement does not have a widespread fine effect on paintings performance, work environment has a significant fine effect on job pleasure, activity delight has a significant nice effect on work performance, job satisfaction can mediate the paintings surroundings on performance. work, and job pleasure cannot mediate reimbursement for work performance.Keywords: Work Environment, Compensation, Job Satisfaction, Job Performance